2019
DOI: 10.1002/aqc.3100
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring long‐term changes in UK grey seal pup production

Abstract: 1. The population size of many species, particularly those in the aquatic environment, cannot be censused directly. Counts, during the breeding season, of one component of the population (e.g. breeding females) are often used as an index to allow investigation of trends. In species, such as grey seals (Halichoerus grypus), for which births are not tightly synchronous, single counts of pups represent an unknown proportion of the total number of pups born (pup production), and thus of breeding females (i.e. each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 46 publications
(113 reference statements)
0
28
0
Order By: Relevance
“…show different dynamics to those of harbour seals (Russell, Morris, Duck, Thompson, & Hiby, 2019;Thomas et al, 2019). Both pup production and population estimates for grey seals in the West Scotland and the Western Isles SMUs were increasing until the mid-1990s…”
Section: Robustness Of Trendsmentioning
confidence: 97%
“…show different dynamics to those of harbour seals (Russell, Morris, Duck, Thompson, & Hiby, 2019;Thomas et al, 2019). Both pup production and population estimates for grey seals in the West Scotland and the Western Isles SMUs were increasing until the mid-1990s…”
Section: Robustness Of Trendsmentioning
confidence: 97%
“…Although predation is a limiting factor on survival of many newly-independent animals, such as cheetahs Ancinonyx jubatus (Laurenson 1994) and passerine birds (Sullivan 1989), and predation events on weaned grey seal pups have been recorded in the UK (Brownlow et al 2016), there is little evidence that predation has a population-level impact on first-year survival in UK grey seals. Indeed, an agestructured Bayesian model revealed that the grey seal population in Orkney reached apparent carrying capacity in the early 2000s, driven by density-dependence acting on pup survival (Thomas et al 2019), likely through processes at-sea related to food availability (Russell et al 2019). Furthermore, it is estimated that newly-weaned pups have an average of 36 days to feed successfully before their protein reserves are critically depleted (Bennett et al 2007).…”
Section: Ontogenetic Changes In Movement Strategiesmentioning
confidence: 99%
“…The abundance of grey seals around Britain has been increasing since the 1960s and the total population was estimated at 141,000 (95% CI 117,500-168,500) in 2016 (SCOS, 2017). Regionally, numbers have been more or less stable on the west of Scotland since the 1990s and in Orkney since the 2000s, albeit with some interannual variation; however, numbers continue to increase in the North Sea (Thomas, Russell, Duck, Morris, Lonergan, Empacher, Harwood, 2019;Russell, Morris, Duck, Thompson & Hiby, 2019).…”
Section: Introductionmentioning
confidence: 99%